A Critical Analysis of Reforming LPP TVRI as a Public Communication Medium in the Digital Era - Prasetya, Bambang Jaka; Sadono, Teguh Priyo; Palupi, Merry Fridha Tri (Kirana Publisher (KNPub), 2025)
This article critically examines the implementation of Government Regulation (PP) No. 13 of 2005 concerning Public Broadcasting Institutions (LPP) of the Republic of Indonesia Television (TVRI) in the last two decades. This study assesses the effectiveness, challenges, and institutional transformation of LPP TVRI in facing an increasingly complex digital media landscape. Through a policy evaluation and analysis of institutional documents, this study reveals a gap between normative mandates and implementation practices in the field. The findings show that the reform of LPP TVRI has not been fully adaptive to the demands of digitalization and public participation. In addition, the emergence of Government Regulation No. 4 of 2024 strengthens the urgency of updating the paradigm of public media governance in Indonesia. TVRI's reform as a public communication medium in the digital era requires more open, innovative, and accountable governance.